Pricing Challenges Facing Maine’s Utility Regulators - Welch, Thomas (Maine Policy Review, 1994)
Decisions concerning the pricing of public utilities are rarely made without controversy. Electric utilities have garnered the lion’s share of the attention in recent months because of the rising cost to consumers of electricity, despite surplus generating capacity and relatively cheap power available on the open market. But other regulated utilities—natural gas, telecommunications, and water—also face important pricing issues in the months ahead. The 1994 conference, sponsored by the Margaret Chase Smith Policy Center’s Project for the Study of Public Regulation and the Environment [PURE], explored several of these issues earlier this year. An important Maine perspective on pricing issues was provided by the chairman of the state’s Public Utilities Commission, Thomas L. Welch who cautioned against making public policy decisions that invest too heavily in narrow assumptions about what might happen in the future. Among other things, he underscored the importance of public acceptance of new policies if those policies are to be effective.